Analysis of Carbon Availability in the Sirimau Mountain Protected Forest Area, Ambon City - Riry, Roberth Berthy; Lasaiba, Mohammad Amin (Universitas Pattimura, 2022)
This study aims to (1) determine the amount of carbon availability in various land uses in the protected forest area of Mount Sirimau, Ambon City, and (2) determine the potential for CO2 absorption based on land use in the protected forest area of Mount Sirimau, Ambon City. The method in this study consisted of making land use maps, measuring plant biomass, and laboratory work. The results showed that the total carbon availability in the protected forest of Mount Sirimau was 418.98 tons/ha, which came from tree carbon stocks, 402.25 tons/ha (96%), and undergrowth, 16.69 tons/ha (4% ). Based on land use, the most extensive carbon stocks came from primary dryland forest land use of 187.59 tons/ha, secondary dryland forest at 100.48 tons/ha, shrubs at 32.59 tons/ha (7.78%), dry agriculture land at 31.41 tonnes/ha (7.5%), mixed dryland agriculture 59.25 tonnes/ha (14.14%), savanna 6.78 tonnes/ha (1.62%) and settlements 0.84 tonnes/ha (0.2%). The potential for carbon dioxide absorption by vegetation in the protected forest of Mount Sirimau is 1,537.50 tons CO2/ha. The most considerable absorption came from tree-level vegetation of 1,476.25 tons CO2/ha or 96% of the total CO2 absorption. Based on land use, primary dryland forest has the most remarkable ability to absorb CO2, namely 688.45 tonnes of CO2/ha or 44.78% of the total CO2 absorption.